Modelagem do uso e conservação dos recursos da geodiversidade no município de São Thomé das Letras - MG - Camila Ragonezi Gomes Lopes (2015)
Sort the space occupation is a challenge that requires the integration of variables that fulfil specific criteria related to different goals. In Minas Gerais context, where the history and economic development are closely linked to mining, it is important to analyse the spatial dynamics of this activity on a territorial perspective, and the didactic educational potential. This study aims to build regional scenarios that focus on the integration of mining activity with geoconservation measures in São Thomé das Letras, Minas Gerais. The method that will be employed consists of literature review, characterization of the study area, spatial dynamic modelling linked to geotechnology (Geographic Information Systems - GIS, Remote Sensing and GIS) and multi-criteria analysis for the scenarios construction. The results will indicate potential areas for mining exploration, to Geoconservation and integration of both. It is hoped that this work can support the spatial planning of São Thomé das Letras, assist the conversion of mining areas, and enhance the historic, tourist, educational and educational potential of mining in São Thomé das Letras.